ADAPTATION OF COMMUNITY ADMINISTRATION IN CIREUNDEU INDEPENDENCE ON ENVIRONMENT IN MAINTAINING LOCAL WISDOM - Sonia Shalihah, - (2019)
This research is motivated by the indigenous people of Kampung Cirendeu who consume staple foods that are different from most Indonesian people, namely by consuming rice from cassava (cassava) called cassava constellations that they grow themselves. In this case the Cireundeu indigenous people must adapt to the surrounding environment so that they are able to overcome the environmental conditions that occur. This study aims to determine the adaptation of the Cireundeu community to its environment and the efforts of the Cireundeu indigenous people to maintain local wisdom. This qualitative research uses phenomenology methods. Informants in this study included traditional leaders, leaders and indigenous elders, Data collection techniques used were participant observation, in-depth interviews, and documentation. The data analysis technique uses qualitative-verification data analysis. The results obtained from the study show that 1). In adaptation to the environment. Cireundeu community understands that geographic factors such as climate, soil, slope and rock are also very influential for life. The environment they live in is not suitable for planting rice, so in this case they choose to grow cassava 2). The consumption of rice (cassava rice) is a culture of Cireundeu society, another reason the people of Cireundeu consume cassava rice in an effort to maintain local wisdom believes that if they continue to consume rice, then one day they will starve because the number of people continues to grow and the availability of agricultural land is increasingly little is due to the establishment of residential areas, so they are looking for staple foods, namely Rasi (cassava rice) that will support their food security and still maintain good natural fertilizers for the cassava species there. In addition, the researchers also recommended that the Cirendeu indigenous people continue to preserve, maintain and maintain local wisdom as an example of a community that supports sustainable development. Keyword: Adaptation, local wisdom, traditional village.